Impact Of Heavy Metals On Water And Soil Environment Of A Paint Industry - Jolly, YN; Hossain, A; Sattar, A; Islam, A (Journal of the Bangladesh Chemical Society, 2013)
A study on the heavy metal impact of a paint industry effluent on the surrounding water and soil environment was carried out. This investigation included a variety of sample types essentially related to the impact assessment. The effluent samples collected from Berger Paints Bangladesh Ltd., Savar, were found to contain K, Ca, Mn, Fe, Zn and Sr with the mean concentrations of 9.78, 221, 0.027, 0.031, 0.067 and 0.29 mg L-1, and values of pH, EC, TDS, TSS, BOD and COD measured in those samples were 5.8, 1.28 mS cm-1, 1084 mgL-1, 66 mg L-1 and 101 mg L-1, respectively. The mean concentrations of K, Ca, Mn, Fe, Zn and Sr in groundwater samples and the values of pH, EC, TDS, TSS found in those samples were 1.58, 16.27, 0.25, 0.013, 0.058 and 0.14 mg L-1 and 7.2, 0.17 mS cm-1, 145 mg L-1, and 10 mg L-1, respectively. The effluent receiving pond water showed the presence of K, Ca, Fe, Zn, Br, and Sr with the average concentrations of 3.37, 23, 0.32, 0.37, 0.03 and 0.11 mg L-1, respectively. The respective concentrations of elements-K, Ca, Mn, Fe, Cu, Zn, Br, Rb and Sr detected in aquatic plant (Halenchi shak) growing on effluent receiving pond water were 46400, 4846, 148, 174, 12.7, 62, 37, 124 and 23 mg kg-1. The mean contents of K, Ca, Ti, Mn, Fe, Cu, Zn, Rb and Sr in samples of paint industry-adjacent agricultural land soil were 10128, 8131,5260, 642, 24025, 56, 84, 135 and 138 mg kg-1, respectively. The mean concentrations of elements in pond water (K: 2.49, Ca: 15.2, Fe:0.19, Zn: 0.24, Br: 0.03 and Sr: 0.11 mgL-1), Halenchi shak (K: 42259, Ca: <1837, Mn: <58, Fe: 163, Cu: <14, Zn: 47, Br: 20, Rb: 68 and Sr: 16 mg kg-1) and soil samples (K: <5491, Ca: <3300, Ti: 5034, Mn: 514, Fe: 34660, Cu: 58, Zn: 65, Rb: 135 and Sr: 38 mg kg-1) collected from a pollution free non-industrial zone indicated lower levels for the same parameters than those in corresponding above mentioned effluent-polluted samples. Journal of Bangladesh Chemical Society, Vol. 25(2), 159-165, 2012 DOI: http://dx.doi.org/10.3329/jbcs.v25i2.15068